EFEKTIFITAS PENYUSUNAN PROGRAM BIDANG BIMBINGAN KARIER DI SMA SE-PROVINSI BENGKULU - tri aprizal; susi Hardianti (Guidance and counseling the university of Prof. Dr. Hazairin. SH, 2018)
This study aims to find out: (1) a description of how the teacher guidance and counseling analyze the needs of learners to develop programs field of career counseling in high school Se Bengkulu province, (2) a description of how the teacher guidance and counseling plan organizer program fields career guidance in high school Se Bengkulu province, (3) a description of how the teacher guidance and counseling melakasanakan program field of career counseling in high school Se Bengkulu province, (4) a description of how the teacher guidance and counseling evaluate the results of exercising their program areas of career counseling in high school Se Province Bengkulu, (5) a description of how the teacher guidance and counseling melaporakan results of program implementation in the field of career counseling SMA Se Bengkulu province, (6) a description of how the follow-up guidance and counseling teachers to the field of career guidance program in SMA Se Bengkulu Province. In this study, the analysis is the Program Development Effectiveness in the field of career guidance High School Se Bengkulu Province. The method in this study using a quantitative approach. The population in this study were 116 high school Se Bengkulu province. The sample in this study as many as 61 people. Data collection techniques in this study using a questionnaire. Data analysis techniques in the study of statistical techniques. Once the data is collected and analyzed obtained the following results: The level of needs analysis is carried to the preparation program of career counseling in high school field Se Bengkulu province, in keseluruahan have been effective, but there are some high school in effective gori said. The level of planning that is carried to the preparation program of career counseling in high school field Se Bengkulu province, in keseluruahan in the category effectively. The level of implementation of career counseling in high school field Se Bengkulu province, in keseluruahan be at an effective level, but there are some high school has enough effective, ineffective. The level of program evaluation in the field of career counseling SMA Se Bengkulu province, in keseluruahan are at a level very effective, but there are some high school has a quite effective, and ineffective. The level of reporting program of career counseling in high school field Se Bengkulu province, in keseluruahan are at a level very effective, but there are some high school has effective enough. The level of follow-up program of career counseling in high school field Se Bengkulu province, in keseluruahan are at a level very effective, but there are some high school has effective enough.